Group portrait of Heald Business College Students - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::; Tucker, John O., d. 1928 (studio):::Contributor::::::::::::
Group portrait showing Heald Business College students assembled on an unidentified lawn.